2022
DOI: 10.1136/jitc-2021-003663
|View full text |Cite
|
Sign up to set email alerts
|

Loss of YTHDF1 in gastric tumors restores sensitivity to antitumor immunity by recruiting mature dendritic cells

Abstract: BackgroundGastric cancer (GC) is one of the most common cancer worldwide. We analyzed the expression of m6A regulatory genes in GC cohorts and revealed that YTHDF1 was uniquely upregulated in GC as compared with adjacent normal tissues. In this study, we analyzed the role of YTHDF1 in GC cells and modulation of the tumor immune microenvironment.MethodsThree GC cohorts (cohort 1, n=101; cohort 2, n=278, and the Cancer Genome Atlas cohort, n=375) were analyzed for YTHDF1 expression. Function of YTHDF1 in GC was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 37 publications
(44 reference statements)
1
31
0
Order By: Relevance
“…As a consequence, ICB therapeutic response is significantly enhanced in YTHDF1knockout mice as compared to wildtype mice. Consistently, our recent study implied the role of YTHDF1 in repressing DCs function in GC [17]. Loss of YTHDF1 in tumor cells leads to the recruitment of mature DCs in the tumor, which in turn promotes the infiltration of T helper cells and cytotoxic T cells, as well as the increased production of cytotoxic cytokines.…”
Section: The Impact Of Ythdf1 On Immunotherapysupporting
confidence: 85%
See 3 more Smart Citations
“…As a consequence, ICB therapeutic response is significantly enhanced in YTHDF1knockout mice as compared to wildtype mice. Consistently, our recent study implied the role of YTHDF1 in repressing DCs function in GC [17]. Loss of YTHDF1 in tumor cells leads to the recruitment of mature DCs in the tumor, which in turn promotes the infiltration of T helper cells and cytotoxic T cells, as well as the increased production of cytotoxic cytokines.…”
Section: The Impact Of Ythdf1 On Immunotherapysupporting
confidence: 85%
“…In terms of clinical application, YTHDF1 is reported to be an independent marker for the diagnosis and prognosis of GI cancer [ 17 , 29 ]. Interestingly, several studies have suggested that YTHDF1 and its downstream signaling pathways might serve as novel therapeutic targets against GI cancers, given the accumulating evidence showing its role in mediating drug resistance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, YTHDF1 induces lysosomal protease expression by recognizing its m 6 A methylation-tagged mRNA and enhancing translation efficiency, further resulting in the inability of DCs to consistently induce tumor neoantigen production and impeding antigen-specific activation of CD8 + T cells [ 123 ]. Conversely, YTHDF1 deficiency in gastric cancer promotes the recruitment of mature DCs, which further stimulate MHCII expression and IL-12 secretion, in turn, increasing CD4 + and CD8 + T cell infiltration and IFN-γ secretion that potentially contribute to restoration of tumor immune sensitivity [ 124 ]. Therefore, YTHDF1 deletion may enhance antitumor immunity by facilitating interactions with DCs, rather than promoting their differentiation and proliferation, supporting a potential role of YTHDF2 as a tumor immunosuppressive factor.…”
Section: A Methylation Remodels Immunosuppressive Tme By Directly Aff...mentioning
confidence: 99%